Preparation method of quaternary coated superfine ammonium perchlorate
The surface coating of ultrafine ammonium perchlorate was solved by the quadrilateral coating method, which solved the safety problems caused by its high mechanical sensitivity, and achieved low sensitivity, low hygroscopicity and high dispersion of ultrafine ammonium perchlorate powder The preparation of the product significantly improves its safety performance and energy performance.
Patent Information
- Application Number
- CN202411706664.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
AI Technical Summary
The high mechanical sensitivity of ultrafine ammonium perchlorate leads to low safety of propellants and mixed explosives formed with other explosives, and its introduction will improve the mechanical sensitivity of propellants and mixed explosives, affecting safety performance.
The surface coating method is adopted to coat ultrafine ammonium perchlorate, and substances such as nitrified cotton, fluoroelastomer, 2,4-dinitroblastomer, octadecanylamine and nanographite are used as coating agents. , by combining mechanical ball milling method and jet refining method, ultrafine ammonium perchlorate powder with low sensitivity, low hygroscopicity and high dispersion were prepared.
It significantly reduces the sensitivity of ultrafine ammonium perchlorate, especially friction and impact, improves its stability and safety performance in high humidity environments, and has almost no impact on the energy performance and internal ballistic performance of the propellant. .
Smart Images

Figure CN119431087A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of explosives and pyrotechnics, and in particular to a method for preparing quaternary coated ultrafine ammonium perchlorate. Background Art
[0002] Ammonium perchlorate (AP, NH4ClO4) is an oxidant with high density and high effective oxygen content. Its combustion and detonation products are both gases. It has very good comprehensive performance and is widely used in propellants and mixed explosives. However, AP has high mechanical sensitivity, which leads to low safety of propellants and mixed explosives formed by it with RDX, HMX, polymers, Al powder, etc., which limits the application of AP in ammunition. In addition, for solid propellants, in order to increase their burning rate and reduce the combustion pressure index, except for coarse particles of AP (d 50 ≈100~300μm), an appropriate amount of ultrafine AP (d 50 ≈3~5μm). Moreover, compared with coarse AP particles, the introduction of ultrafine AP will further increase the mechanical sensitivity of propellants and mixed explosives, which seriously deteriorates the safety performance of solid propellants and mixed explosives during preparation, transportation and use. Therefore, ultrafine AP must be desensitized before practical use.
[0003] At present, the most effective way to reduce the sensitivity of ultrafine AP is to coat its surface. In fact, in the field of explosives, it is very common to study the surface coating and sensitivity reduction of certain high-sensitivity explosives. However, it cannot be said that substances that can be coated on the surface of other explosives can also be coated on the surface of ultrafine AP; and it cannot be said that coatings that can reduce the sensitivity of other explosives can also reduce the sensitivity of ultrafine AP. Of course, there are literature reports that the sensitivity of ultrafine AP decreases after coating with substances such as trinitrotoluene (TNT) or polyazide glycidyl ether (GAP). These are relatively good research ideas, because TNT and GAP are both energetic and low in sensitivity. Therefore, when they are coated on the surface of ultrafine AP, not only the sensitivity of ultrafine AP is reduced, but also the energy performance of ultrafine AP is not seriously damaged. Unfortunately, current reports have shown that these substances can only significantly reduce the sensitivity of ultrafine AP when the coating amount is large; for example, when the coating amount is 8wt.% or less, the sensitivity reduction effect is very limited, and only 10-15% of the coating agent can achieve a good sensitivity reduction effect, which seriously affects the process performance and energy performance of the subsequent formulation.
[0004] After extensive research, it was found that there are four main reasons for this phenomenon. First, the sensitivity of energetic materials such as TNT and GAP is not extremely low, so if you want to reduce the sensitivity of AP, you must add a large amount of them; second, taking ultrafine AP as the object, from the perspective of the interface, materials such as TNT and GAP have poor wettability on the surface of ultrafine AP, while paraffin wax (WAX), thermoplastic polyurethane (TPU), fluororubber, Estane and other materials that have good wettability on ultrafine AP are energy-free and inert substances. Adding a large amount of them will inevitably affect the energy performance of ultrafine AP; third, due to the large amount of polymer coated on the surface of ultrafine AP, the friction between AP particles is greatly increased compared to when it is not coated, so when the coating amount is low, the sensitivity of ultrafine AP does not decrease significantly; fourth, AP is a hygroscopic substance that absorbs moisture and clumps during storage, and the anti-hygroscopicity of the coatings reported so far is very limited. Therefore, in an environment with high humidity, the moisture in the air will destroy the coating layer on the surface of the ultra-fine AP, resulting in adhesion and agglomeration, which not only changes the particle size and particle size distribution of the ultra-fine AP, but also causes the sensitivity of the ultra-fine AP to rise again. Therefore, in order to solve the above four problems, the present invention uses four substances in a targeted manner and simultaneously performs surface coating treatment on the ultra-fine AP, which greatly alleviates the negative effects caused by these problems, so that when the coating amount is low, the sensitivity of the ultra-fine AP will be significantly reduced. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing quaternary coated ultrafine ammonium perchlorate.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention relates to a method for preparing quaternary coated ultrafine ammonium perchlorate, comprising the following steps:
[0008] Step 1, subjecting coarse particles of ammonium perchlorate to ball milling to obtain ultrafine ammonium perchlorate powder;
[0009] The present invention adopts a mechanical ball milling method; the ball mill model is a PM400 high-energy planetary mill produced by German RETSCH Company; the grinding beads are zirconium beads with a diameter of 5 mm (ZrO2 doping mass content of 2% to 10% Y2O3), Shandong Zibo Yubang Industrial Ceramics Co., Ltd. The ball mill is equipped with four ball milling jars, each with a capacity of 250 mL, and there are four symmetrical fixed ball milling jars in the ball mill. The specific method is:
[0010] (1) Place in each jar: 50 g of coarse AP, 160 ml of anhydrous ethanol, and 250 g of zirconium beads.
[0011] (2) Seal the four jars and place them in the ball mill and secure them in place.
[0012] (3) Set the speed to 350 rpm, rotate forward for 2 minutes, then reverse for 2 minutes, alternating between the two cycles; the ball milling time is 3 hours without stopping the machine.
[0013] (4) After the ball milling is completed, the machine is stopped, the material is taken out, the material is filtered out, and freeze-dried for 24 hours to obtain white ultrafine AP powder for standby use.
[0014] Compared with the jet refining method, the mechanical ball milling method adopted in the present invention has the characteristics of high technical output, small amount of solvent used, low reaction temperature, uniform powder particle size distribution, short cycle, non-toxicity, etc., and is a green and environmentally friendly explosive refining method.
[0015] Step 2, quaternary coating of ultrafine ammonium perchlorate powder:
[0016] (1) Nitrocellulose (NC, [C6H7N3O 11 ] n ,CAS No.:9004-70-0), fluorine rubber (FE2602, copolymer of vinylidene fluoride and hexafluoropropylene), 2,4-dinitroanisole (DNAN, C7H6N2O5,CAS No.:119-27-7), octadecylamine (C 18 H 39 N, CAS No.: 124-30-1) was dissolved in a mixed azeotropic solvent consisting of acetone and ethyl acetate to obtain solution A;
[0017] (2) Nanographite 50 =30~50nm, Guangzhou Hongwu Material Technology Co., Ltd.) and ultrafine ammonium perchlorate powder are added to solution A, and ultrasonically stirred to obtain a thin sludge mixture;
[0018] (3) Place the thin sludge mixture into a culture dish and dry it in a water bath oven.
[0019] Preferably, in step 1, the particle size of the ultrafine ammonium perchlorate powder is 2 to 5 μm.
[0020] Preferably, in step 2, the usage ratio of nitrocellulose, fluororubber, 2,4-dinitroanisole, octadecylamine, nanographite, and ultrafine ammonium perchlorate powder is 1.5:0.5:2.0:0.5:1.5:94.
[0021] Preferably, the mass fraction of acetone in the mixed azeotropic solvent is 81 wt.%, and the mass fraction of ethyl acetate is 19 wt.%.
[0022] Preferably, the nanographite has a d 50 It is 30 to 50nm.
[0023] Preferably, the drying temperature is 50° C. and the drying time is 24 hours.
[0024] The effects of each component used in the present invention are as follows:
[0025] Nitrocellulose NC is a high molecular energetic material with very high energy. It is often used as a binder in double-base propellants. It has very good wettability on the surface of ultrafine AP particles and is used as a film-forming agent in the present invention. Fluororubber FE2602 is a fluorine-containing fluororubber. When combined with NC, it can significantly improve the film-forming property and viscosity of NC, improve the plasticity of NC, and greatly reduce the sensitivity of NC (after all, NC is also a nitrate-based energetic material). Therefore, NC combined with a small amount of FE2602 is a very excellent low-sensitivity composite film-forming agent.
[0026] 2,4-Dinitroanisole DNAN is a high explosive with extremely low sensitivity but high energy. Its sensitivity is much lower than that of trinitrotoluene (TNT), while its energy is close to that of TNT. Since DNAN is almost the lowest sensitivity among the currently known high explosives, its various sensitivities are close to those of inert substances, and its solubility in various solvents is very high, it is used as an energetic desensitizer in the present invention. In addition, DNAN is a waxy solid, so it not only has a very good desensitization effect, but also has certain film-forming properties and hydrophobicity. Moreover, DNAN is a common chemical intermediate, its price is much lower than that of TNT, and it can be purchased through normal channels without the need for special procedures and controls.
[0027] Octadecanamine is a highly effective surfactant and is used as a hydrophobic agent in the present invention. When a small amount of octadecaneamine is contained in the coating layer of the ultra-fine AP, it will not absorb moisture or form lumps when left for a long time.
[0028] Nanographite acts as a lubricant. After nanographite is coated on the surface of ultrafine AP particles, the friction between ultrafine AP particles will be greatly reduced, and the particles will be very smooth, which plays a critical role in greatly reducing the friction sensitivity of ultrafine AP. Moreover, when the friction on the surface of ultrafine AP particles is greatly reduced, the dispersibility of the powder will also be greatly improved. The reason why the present invention uses nanographite is: on the one hand, the constituent element of nanographite is carbon, which will be completely oxidized into gaseous CO2 during the combustion process and release a large amount of heat, so adding a small amount of nanographite will not theoretically reduce the energy performance of ultrafine AP; on the other hand, the specific surface area of nanographite is much larger than that of micron graphite, about 1000 times that of micron graphite. Therefore, in the coating, only a small amount of nanographite (1.5wt.%) can achieve the effect of adding 10wt.% or even 15wt.% micron graphite. For AP, graphite is an inert substance after all, so the less the better.
[0029] The mixed solvent composed of acetone and ethyl acetate is an azeotropic solvent, wherein the mass fraction of acetone is 81wt.%, and the mass fraction of ethyl acetate is 19wt.%. Acetone and ethyl acetate form an azeotropic solvent with an azeotropic point of 58°C. The advantages of using an azeotropic solvent are: first, the azeotropic solvent has a stronger solubility for NC, DNAN and octadecylamine than a single solvent, which is conducive to the coating when a small amount of solvent is used; second, the boiling point of the azeotropic solvent is low, only 58°C, so when it is dried, the oven temperature can be controlled within 50°C, which greatly improves the safety of the operation process during mass production and shortens the time required for drying. In fact, since a large amount of energetic materials are processed in the present invention, the most dangerous step is the drying process; and the use of an azeotropic solvent reduces the operating temperature and required time of this link, improving the safety of the operation; in addition, the use of a mixed solvent also greatly improves the dispersibility of nanographite powder in the solvent.
[0030] The present invention has the following advantages:
[0031] (1) The ultrafine AP prepared by the present invention has the following advantages: low sensitivity, low moisture absorption, and good dispersibility;
[0032] (2) The mixed solvent (mass fraction of acetone is 81 wt.%, mass fraction of ethyl acetate is 19 wt.%) used in the present invention is an azeotropic solvent having the characteristics of high solubility and low azeotropic point.
[0033] (3) The raw materials involved in the present invention are all clean and easily available, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM photo of the uncoated ultrafine AP particles as a whole in Example 1;
[0035] Figure 2 This is a SEM photo of the local surface of the uncoated ultrafine AP particles in Example 1.
[0036] Figure 3 This is a SEM photograph of the local surface of the ultrafine AP particles after quaternary coating prepared in Example 1;
[0037] Figure 4 1 is a graph showing the test results of differential scanning calorimetry (DSC) of the coarse particle AP, ultrafine AP, and coated ultrafine AP in Example 1;
[0038] Figure 5 It is the linear relationship diagram of the coarse particle AP, ultrafine AP and coated ultrafine AP fitted by the Kissinger equation;
[0039] Figure 6 This is a diagram of the kinetic compensation effects of three materials: coarse-grained AP, ultrafine AP, and coated ultrafine AP. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are only further descriptions of the present invention, but the protection scope of the present invention is not limited to the following embodiments.
[0041] Example 1
[0042] This embodiment relates to a method for preparing a quaternary coated ultrafine ammonium perchlorate, comprising the following steps:
[0043] Step 1, the preparation of ultrafine ammonium perchlorate powder adopts mechanical ball milling method: the ball mill model is PM400 high-energy planetary mill produced by RETSCH Company of Germany; the grinding beads are zirconium beads with a diameter of 5 mm (ZrO2 doped with 2% to 10% Y2O3 by mass), produced by Shandong Zibo Yubang Industrial Ceramics Co., Ltd. The ball mill is equipped with four ball milling jars, each with a capacity of 250 mL, and there are four symmetrical positions for fixing jars in the ball mill; the specific method is as follows: (1) First, put: 50 grams of coarse AP particles, 160 milliliters of anhydrous ethanol, and 250 grams of zirconium beads in each jar; (2) Seal the four jars, put them into the ball mill and fix them in the jar position; (3) Set the speed to 350 rpm, after 2 minutes of forward rotation, reverse for 2 minutes, and alternately carry out; the ball milling time is 3 hours, without stopping in the middle; (4) After the ball milling is completed, stop the machine, take the material, filter out the material, and freeze-dry it for 24 hours to obtain white ultrafine AP powder, see Figure 1 As shown in the figure, the ultrafine AP particles after ball milling are irregular potato-shaped and have a particle size of 2 to 5 μm. Figure 2 As shown, the surface of the uncoated ultrafine AP particles is very smooth.
[0044] Step 2: Quaternary surface coating of ultrafine AP
[0045] (1) 1.5 g of nitrocellulose (NC), 0.5 g of fluororubber (FE2602, a copolymer of vinylidene fluoride and hexafluoropropylene), 2.0 g of 2,4-dinitroanisole (DNAN), and 0.5 g of octadecylamine were completely dissolved in 50 g of a mixed azeotropic solvent consisting of acetone and ethyl acetate to obtain a solution A; wherein the mass fraction of acetone is 81 wt.%, and the mass fraction of ethyl acetate is 19 wt.%;
[0046] (2) 1.5 g of nanographite (d 50 =40nm) and 94g of ultrafine AP dry powder were added to the obtained solution A, and stirred with a glass rod to form a thin sludge-like mixture while being subjected to strong ultrasound. After mixing for 30 minutes, the material was basically uniform;
[0047] (3) The sludge mixture was placed in a larger culture dish, and then placed in a water bath oven and dried at 50°C for 24 hours to obtain coated ultrafine AP powder. Figure 3 As shown, the surface of the ultrafine AP particles after quaternary coating treatment is rough, and the existence of the coating layer can be clearly seen, and the coating layer is very dense.
[0048] See Figure 4 As shown, (a) is a differential scanning calorimetry (DSC) test result diagram of coarse particle AP; (b) is a differential scanning calorimetry (DSC) test result diagram of ultrafine AP; (c) is a differential scanning calorimetry (DSC) test result diagram of AP after quaternary surface coating;
[0049] For all samples (coarse-grained AP, ultrafine AP, and coated ultrafine AP), there is a sharp endothermic peak at around 250°C, which represents the crystal transformation process of AP. In addition, for all samples, a large exothermic peak appeared between 350 and 450°C, which represents the high-temperature thermal decomposition process of AP. All thermal analysis processes are consistent with those reported in the literature, which shows that neither ball milling nor coating has a destructive effect on the structure of the AP body.
[0050] In addition, some thermodynamic and kinetic parameters of each sample (coarse particle AP, ultrafine AP, and coated ultrafine AP) were calculated using the high temperature decomposition peak temperature (Tp) at different heating rates in the DSC curve. The results are shown in Table 1.
[0051] Table 1
[0052]
[0053] In Table 1: T p is the exothermic peak temperature in the DSC curve at different heating rates;
[0054] ΔH ≠ is the activation enthalpy;
[0055] ΔG ≠ is the activation free energy;
[0056] ΔS ≠ is the activation entropy;
[0057] E K is the activation energy of thermal decomposition calculated using the Kissinger equation;
[0058] A K is the pre-exponential factor calculated using the Kissinger equation;
[0059] k is the rate constant, k = A K Exp[-EK / (T p ·R)];
[0060] Table 1 shows that when the heating rate is fixed, the T p The value should be greater than the T of the ultra-fine AP p value, while the T p The value is greater than the T of the AP coated in Example 1. p This shows that ultrafine and coating treatments can significantly reduce the high-temperature thermal decomposition temperature of AP, which is also a promoting effect on the thermal decomposition of AP. In addition, the activation energy EK of the coated AP in Example 1 is much smaller than the EK value of ultrafine AP, while the EK value of ultrafine AP is smaller than the EK value of coarse-grained AP, which once again shows that ultrafine treatment and surface coating treatment significantly improve the thermal decomposition activity of AP. In particular, the surface coating treatment significantly reduces the thermal decomposition activation energy of AP, which shows that the coating layer has a strong promoting effect on the thermal decomposition of AP.
[0061] See Figure 5 As shown in the figure, the linear relationship of the Kissinger equation fitting line is very good, which shows that the thermodynamic calculation results are very accurate. In addition, for the three samples (coarse particle AP, ultrafine AP, and coated ultrafine AP), there is also a very high linear relationship between EK and lnAK, see Figure 6 As shown, the thermodynamic mechanism of thermal decomposition of the three samples is consistent, which is the thermal decomposition mechanism of AP. This also shows from another perspective that neither ball milling nor coating has changed the main structure of AP.
[0062] As shown in Table 2, the impact sensitivity and friction sensitivity of the quaternary surface-coated ultrafine AP prepared in Example 1 are significantly lower than those of the uncoated ultrafine AP and coarse-grained AP, among which the impact sensitivity and friction sensitivity of the ultrafine AP are both higher than those of the coarse-grained AP. The thermal sensitivity of the quaternary surface-coated ultrafine AP prepared in Example 1 is equivalent to that of the coarse-grained AP, and both are slightly lower than the thermal sensitivity of the uncoated ultrafine AP. In addition, the hygroscopicity of the quaternary surface-coated ultrafine AP prepared in Example 1 is much lower than that of the uncoated ultrafine AP and coarse-grained AP. These data show that after ultrafine processing and quaternary coating, the sensitivity and water absorption of AP are significantly reduced, among which the reduction in friction sensitivity is the largest and most obvious. Therefore, after only coating with a 6wt.% coating layer, and it is an energetic coating layer, the friction sensitivity can be reduced from 100% to 8%, indicating that the four coatings selected by the present invention are all very effective and hit the key point of the sensitivity reduction mechanism.
[0063] Table 2
[0064]
[0065] In Table 2, H50 H is the impact sensitivity characteristic drop height, 50 The larger the value, the lower the impact sensitivity of the agent; P is the explosion percentage of friction sensitivity, the larger the value, the higher the friction sensitivity of the agent; T 5s The 5-second burst point of the potion, T 5s The higher it is, the lower the thermal sensitivity of the agent. E is the apparent activation energy of thermal decomposition of the agent during the thermal sensitivity test, which has little to do with thermal sensitivity.
[0066] Therefore, in general, the coating treatment of the surface of AP in the present invention not only greatly reduces the friction sensitivity, impact sensitivity and thermal sensitivity of ultrafine AP, but also greatly promotes the thermal decomposition performance of ultrafine AP.
[0067] The quaternary surface-coated ultrafine AP and the uncoated ultrafine AP prepared in Example 1 of the present invention were applied to HTPB propellant to prepare propellant strips, and the burning rate and combustion pressure index of the strips were tested at 2-12 MPa. At the same time, the standard specific impulse and characteristic velocity of the two propellants were calculated using NASA-CEA2 software. The results are shown in Table 3.
[0068] Table 3
[0069]
[0070] In Table 3, HTPB is hydroxybutyl rubber, TDI is toluene diisocyanate as a curing agent, Example 1 is a propellant prepared using the coated ultrafine AP in Example 1, and Example 2 is a propellant prepared using uncoated ultrafine AP.
[0071] The data in Table 3 show that for the two propellants using coated and uncoated ultrafine AP, their standard specific impulse and characteristic velocity are almost the same, which shows that the coating treatment does not negatively affect the energy performance of the propellant. In addition, for the two propellants using coated and uncoated ultrafine AP, their burning speed at 7MPa has not changed significantly, but the pressure index of the propellant using coated AP has increased, but the increase is not large. The industry stipulates that as long as the combustion pressure index of the propellant is less than 0.5, it has met the practical requirements. Therefore, the coating treatment has no actual effect on the internal ballistic performance of the propellant.
[0072] In summary, the quaternary coating treatment method adopted in the present invention is very effective in reducing the sensitivity of ultrafine AP, especially the friction sensitivity is greatly reduced; in addition, the quaternary coating treatment is also very effective in reducing the hygroscopicity of AP; but it has almost no effect on the energy performance and internal ballistic performance of the propellant.
[0073] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which will not affect the essence of the present invention.
Claims
1. A method for preparing quaternary coated ultrafine ammonium perchlorate, characterized in that: The following steps are involved: Step 1, subjecting coarse particles of ammonium perchlorate to ball milling to obtain ultrafine ammonium perchlorate powder; Step 2, quaternary coating of ultrafine ammonium perchlorate powder: (1) dissolving nitrocellulose, fluororubber, 2,4-dinitroanisole, and octadecylamine in a mixed azeotropic solvent consisting of acetone and ethyl acetate to obtain solution A; (2) adding nano-graphite and ultrafine ammonium perchlorate powder to solution A, subjecting the mixture to ultrasonic treatment and stirring to obtain a sludge-like mixture; (3) Place the thin sludge mixture into a culture dish and dry it in a water bath oven.
2. The method for preparing the quaternary coated ultrafine ammonium perchlorate according to claim 1, characterized in that: In step 1, the particle size of the ultrafine ammonium perchlorate powder is 2 to 5 μm.
3. The method for preparing the quaternary coated ultrafine ammonium perchlorate according to claim 1, characterized in that: In step 2, the usage ratio of the nitrocellulose, fluororubber, 2,4-dinitroanisole, octadecylamine, nanographite, and ultrafine ammonium perchlorate powder is 1.5:0.5:2.0:0.5:1.5:
94.
4. The method for preparing the quaternary coated ultrafine ammonium perchlorate according to claim 1, characterized in that: The mass fraction of acetone in the mixed azeotropic solvent is 81 wt.%, and the mass fraction of ethyl acetate is 19 wt.%.
5. The method for preparing the quaternary coated ultrafine ammonium perchlorate according to claim 1, characterized in that: The nanographite 50 It is 30 to 50 nm.
6. The method for preparing the quaternary coated ultrafine ammonium perchlorate according to claim 1, characterized in that: The drying temperature is 50° C. and the drying time is 24 hours.